Species diversity of macrobenthic invertebrates in the Semenyih River, Selangor, Peninsular Malaysia - Yap, Chee Kong; Ismail, A. Rahim; Ismail, Ahmad; Tan, Soon Guan (Universiti Putra Malaysia Press, 2003)
This study was carried out on one of the rivers in Peninsular Malaysia, the Semenyih River. The river supported diverse macrobenthic invertebrates in which the upstream sampling stations were dominated by Crustacea, Ephemeroptera, Odonata, Gastropoda, Trichoptera, Coleoptera and Diptera while Hirudinea and Oligocheata were the benthic organisms found predominant at downstream stations. Some caddisJly species such as Microstenum similior and Amphipsyche meridiana were found to be potential bioindicators for a cleanecosystem. The resistant worm, Limnodrilus hoffmeisteri, was found to be the most dominant species at the downstream of the river and is considered a potential bioindicator for a polluted ecosystem. Low species diversity and occurrence of resistant worm species indicated that the downstream of the river deteriorated due to water quality degradation. As rapid increases in population growth, industrialization and agricultural activities in Malaysia have caused serious problems to the water quality of many rivers, the macrobenthic invertebrates found along the rivers can be used as bioindicators of the ecotoxicological effects of river pollution in Malaysia.